The lasting harm: witnessing the trial of Ghislaine Maxwell - Osborne-Crowley, Lucia (4th Estate, 2024)
The explosive, behind-the-scenes account of the criminal trial of the century. 'I understand - and sympathise with - the feeling you might have that you already know the Jeffrey Epstein story. But I am not here to tell you a story about Jeffrey Epstein, or even Ghislaine Maxwell. I am here to tell you the stories of ten women, many of whom have never spoken at length before, about the real impact of sexual trauma on their lives.' In November 2021, Ghislaine Maxwell was convicted of five counts of sex-trafficking of minors, and now faces 55 years in prison for the role she played in Jeffrey Epstein's abuse of four girls. The trial was meticulously covered by journalist and legal reporter Lucia Osborne-Crowley, one of only four reporters allowed into the courtroom every day. 'The Lasting Harm' is her account of that trial